Histology sections and scanning electron micrographs of floral buds of Pteridophyllum racemosum - Kong, Doudou; Justus Liebig University Giessen (My University, 2024)
The size of a single photo is about 14MB. The size of a single SEM photo is about 1.25MB. Both SEM graphs and histology sections graphs are formatted as ".TIFF" and can be opened using any image viewer.
Keywords: ddc:580